ANALISIS GAYA BELAJAR PESERTA DIDIK SD N 03 MAKBON KABUPATEN SORONG - Maria J. Kimkurin; Muhammad Faizin; Gika Apia (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Learning at school does not seem to be able to overcome learning difficulties at school, as well as reading difficulties that occur to students at SD N 03 Makbon, Sorong Regency, as many as 17 people have not been able to read fluently. Initial observations show that the approach method used by educators is less effective. The purpose of this study is to find out the learning style of students. Using a qualitative descriptive approach, with 17 respondents, and observation data collection methods as well as interviews. The results of the study show that the most prominent learning style used by students is the visual learning style. This is because students prefer to learn by watching their teachers explain in front of the class